PENERAPAN ASAS PUBLISITAS PADA PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KOTA SAWAHLUNTO PROVINSI SUMATERA BARAT - Wahyu Perkasa Oktavio (UNES Law Review, 2022)
Land registration is important as evidence of strong rights to land rights and to provide legal certainty regarding land rights, as regulated in Article 19 paragraph (1) UUPA. Announcement of the status of ownership of land rights is the principle of publicity in the implementation of land registration. One of the important issues related to legal certainty in the implementation of land registration is the principle of publicity. This principle regulates and guarantees proof of ownership of land rights where each application for registration must be carried out by the announcement of physical data and juridical data for a certain time. The implementation of PTSL 2019 in West Sumatra, one of which is Sawahlunto City, which has been carried out in Tumpuk Tangah Village, Talawi District. This research is a legal research with a descriptive analytical research specification with a normative juridical approach as the main approach and supported by an empirical juridical approach. So it can be concluded how the application of the principle of publicity to the complete systematic land registration in the City of Sawahlunto, West Sumatra Province and the legal impact if the principle of publicity is not applied